A posteriori error estimates of stabilized finite volume method for the Stokes equations. (11th March 2015) - Zhang, Tong; Mu, Lin; Yuan, JinYun
Abstract : In this work, the residual‐type posteriori error estimates of stabilized finite volume method are studied for the steady Stokes problem based on two local Gauss integrations. By using the residuals between the source term and numerical solutions, the computable global upper and local lower bounds for the errors of velocity in H 1 norm and pressure in L 2 norm are derived. Furthermore, a global upper bound of u − u h in L 2 ‐norm is also derived. Finally, some numerical experiments are provided to verify the performances of the established error estimators. Copyright © 2015 John Wiley & Sons, Ltd.